The structure of Chinese adolescents' conscience: A scale and its application. Issue 4 (3rd July 2019) - Bian, Junfeng; Li, Liang; Yan, Liangshi; Li, Ying; Li, Chanyi; Li, Chan
Abstract : Based on traditional Chinese conscience theory, we defined the concept of conscience after reviewing the relevant literature. We constructed a preliminary theoretical model of the conscience structure through in‐depth interviews conducted with a sample of 127 Chinese adolescents and an open‐ended questionnaire conducted with 374 volunteers based on the consensual qualitative research (CQR) method. Then, we developed a preliminary conscience scale questionnaire and surveyed 702 people to obtain data for the development of the final questionnaire. The analysis indicated that the self‐developed questionnaire had good reliability and validity. The revised structure model of conscience in Chinese adolescents includes five dimensions: (a) compassion, (b) honesty and credibility, (c) a sense of right and wrong, (d) filial piety and fraternal duty, and (e) gratitude. Using this scale, we surveyed 1, 009 adolescents in China. We have discussed the characteristic differences in scale scores among different age cohorts, genders, subject disciplines, and places of residence.